Characterization of human high molecular weight kininogen. Procoagulant activity associated with the light chain of kinin-free high molecular weight kininogen (The Rockefeller University Press, 1978)
Human high molecular weight (HMW) kininogen has been isolated and was found to be a single chain protein of approximately equal to 120,000 daltons. Upon digestion with plasma kallikrein bradykinin is generated, and SDS gel electrophoresis of the kinin-free protein reveals an apparent loss in size of 15,000 daltons. The kinin-free kininogen retains full activity as a coagulation factor and consists of two chains: a heavy chain of approximately equal to 66,000 daltons disulfide-linked to a light chain of 37,000 daltons. The heavy chain of HMW kininogen shares antigenic determinants with LMW kininogen and possesses no detectable coagulant activity. The isolated light chain is shown to be responsible for the coagulant activity of HMW kininogen and contains a unique antigenic determinant that distinguishes HMW kininogen from low molecular weight kininogen.